Primary utopian elements in the North Caucasian traditional epic «The Narts»: understanding in the context of contemporary social reality - A. M. Siyukhova; I. A. Abdokova (Вестник Майкопского государственного технологического университета)
Abstract. At the present stage, there is an urgent need to assess various forms of utopian ideas, linking it with the problem of strengthening the traditional values of ethnic communities. The subject of the research is to understand the primary elements of utopia in the Nart epic in the context of contemporary social reality. The main method is the method of structural and functional analysis to identify the role of a specific utopian idea in the structure of the Nart epic as a form of reflection of the socio-cultural forms of existence of the ethnos. The extrapolation method is also used, revealing the general and the specific in the implementation of specific utopian ideas in the modern socio-cultural situation. A typology of utopian elements in the epic has been determined, including miracles associated with food products; with physical strength and extraordinary abilities; with the transformation of the human body; with the ability to influence the weather and daily cycles; with the preservation of eternal youth and beauty; with the onset of social equality. It has been revealed that the utopias of the epic often have a material-objective character and are significant not in themselves, but to the extent that they can be useful for the family. The understanding of utopian changes in social structures is expressed metaphorically, in a symbolic form revealing the essence of the attitude to social inequality. The grains of utopia of the Nart epic in modern social reality have taken various forms of implementation: some have come true and ceased to be utopias, while others have transformed from being perceived as real phenomena into utopian ones. Utopian ideas associated with the reorganization of society remain utopias due to the fact that social ideals are constantly changing.